Distribution of Gold Nanoparticles in the Anterior Chamber of the Eye after Intracameral Injection for Glaucoma Therapy - Tobias Sonntag; Franziska Froemel; W. Daniel Stamer; Andreas Ohlmann; Rudolf Fuchshofer; Miriam Breunig (MDPI AG, 2021)
In glaucoma therapy, nanoparticles (NPs) are a favorable tool for delivering drugs to the outflow tissues of the anterior chamber of the eye where disease development and progression take place. In this context, a prerequisite is an efficient enrichment of NPs in the trabecular meshwork with minimal accumulation in off-target tissues such as the cornea, lens, iris and ciliary body. We evaluated the optimal size for targeting the trabecular meshwork by using gold NPs of 5, 60, 80 and 120 nm with a bare surface (AuNPs) or coated with hyaluronic acid (HA-AuNPs). NPs were compared regarding their colloidal stability, distribution in the anterior chamber of the eye ex vivo and cellular uptake in vitro. HA-AuNPs demonstrated an exceptional colloidal stability. Even after application into porcine eyes ex vivo, the HA coating prevented an aggregation of NPs inside the trabecular meshwork. NPs with a diameter of 120 nm exhibited the highest volume-based accumulation in the trabecular meshwork. Off-target tissues in the anterior chamber demonstrated an exceptionally low gold content. Our findings are particularly important for NPs with encapsulated anti-glaucoma drugs because a higher particle volume would be accompanied by a higher drug payload.